2016
DOI: 10.1371/journal.pone.0164617
|View full text |Cite
|
Sign up to set email alerts
|

Afferent Visual Pathway Affection in Patients with PMP22 Deletion-Related Hereditary Neuropathy with Liability to Pressure Palsies

Abstract: BackgroundThe PMP22 gene encodes a protein integral to peripheral myelin. Its deletion leads to hereditary neuropathy with liability to pressure palsies (HNPP). PMP22 is not expressed in the adult central nervous system, but previous studies suggest a role in CNS myelin development. The objective of this study was to identify potential structural and functional alterations in the afferent visual system in HNPP patients.MethodsTwenty HNPP patients and 18 matched healthy controls (HC) were recruited in a cross-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Pyramidal signs were described by Thomas et al (1997) [ 93 ] in three CMT1A (triploidy of pmp22) patients and Chanson et al (2013) [ 94 ], reported a reduction of white matter volume and cognitive impairment in 70% of CMT1A studied patients. More recently, Brandt et al (2016) [ 95 ] have also described functional, metabolic, and macrostructural alterations in the afferent visual system in eighteen patients with HNPP (pmp22 haploidy). Taking together these previous findings, they further provide some understanding related to the general role of pmp22 expression, especially in the CNS, as well as to normal gene copy number (genic dosage effect).…”
Section: Discussionmentioning
confidence: 99%
“…Pyramidal signs were described by Thomas et al (1997) [ 93 ] in three CMT1A (triploidy of pmp22) patients and Chanson et al (2013) [ 94 ], reported a reduction of white matter volume and cognitive impairment in 70% of CMT1A studied patients. More recently, Brandt et al (2016) [ 95 ] have also described functional, metabolic, and macrostructural alterations in the afferent visual system in eighteen patients with HNPP (pmp22 haploidy). Taking together these previous findings, they further provide some understanding related to the general role of pmp22 expression, especially in the CNS, as well as to normal gene copy number (genic dosage effect).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, OCT finds broad applicability in ophthalmology and dermatology, and more recently, in neurology . With our present study, we account for the increasing interest in rheumatology to employ OCT in diagnosis and drug monitoring by repeatedly visualizing cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The PMP22 gene is mainly expressed in the peripheral nervous system (PNS); however, mRNA and protein can also be found in the central nervous system (CNS) (18). Recent studies suggested the important involvement of the CNS in most patients with PMP22 deletion (18, 19). This is supported by prolonged latencies of visual evoked potentials, neurochemical alterations with decreased N -acetylaspartate (NAA) and creatine (Cre) concentrations, white matter (WM) volume reduction detected by cMRI, cognitive impairment (in 70% of patients), and fractional anisotropy alteration in several WM regions (e.g., in the columns of the fornix) (1820).…”
Section: Discussionmentioning
confidence: 99%